Engineering Three-Dimensional Tumor Models to Study Glioma Cancer Stem Cells and Tumor Microenvironment - Ruiz-Garcia, Henry; Alvarado-Estrada, Keila; Schiapparelli, Paula; Quinones-Hinojosa, Alfredo; Trifiletti, Daniel M. (Frontiers in Cellular Neuroscience, 2020)
Glioblastoma (GBM) is the most common and devastating primary brain tumor, leading to a uniform fatality after diagnosis. Current research supports the fact that a major difficulty in eradicating GBM is the presence of microscopic residual infiltrating disease remaining after multimodality treatment including maximal safe resection and chemoradiation. Glioma cancer stem cells (CSC) have been pinpointed as the treatment-resistant tumor component that seeds ultimate tumor progression. Despite the key role of CSC, the ideal preclinical model to study the genetic and epigenetic landmarks driving their malignant behavior while still simulating an accurate interaction with the tumor microenvironment is still missing. The introduction of three-dimensional (3D) tumor platforms, such as organoids and 3D bioprinting, has allowed for a better representation of the pathophysiologic interactions between glioma CSC and the tumor microenvironment. Thus, these technologies have enabled an accurate study of glioma biology, tumor angiogenesis, treatment resistance, and even perform high throughput screening of drug susceptibility. First, we will review the foundation of glioma biology and biomechanics of the tumor microenvironment, and then the most up-to-date insights about the applicability of these new tools in malignant glioma research.